PEMERINTAHAN MENURUT JOHN LOCKE DAN RELEVANSINYA BAGI DINAMIKA POLITIK DI INDONESIA DALAM KONTEKS PEMILU - Dowa Lego, Efrem Dwi Valencio (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2024)
This paper focuses on John Locke's thoughts on government. The government initiated by John Locke was formed by the people's consent. The people have entrusted the government with the preservation ofthe lives of each of its people. The people play a role as determinants of government, and the government is obliged to serve the people. This thought becomes the theoretical basis for achieving the objectives in this paper. This article aims to show that the Indonesian people play a role in rationally determining a government and that the government in Indonesia is a servant of the people. The method used to achieve that goal is a study of the literature. A literature study is a qualitative research that uses related books as a source of information. This method is supported by the technique of analyzing texts that are directly related to Locke's thought. The discussion on this theme shows that the government was elected rationally by the will of the Indonesian people and therefore the legitimate government must serve the Indonesian people so that every Indonesian can preserve their lives. The survival of each community is in their own hands because they have approved the elected government to regulate their lives for the next 5 years.